THE FIGHT AGAINST GENDER-BASED DISCRIMINATION OF THE CENTRAL CHARACTER IN THE NOVEL YALE NEEDS WOMEN BY ANNE GARDINER PERKINS - Komalasari Kusuma Wardhani; Shita Dewi Ratih P; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
This study discusses about the fight against gender-based discrimination in Yale Needs Women novel by Anne Gardiner Perkins. In the novel, discrimination is derived from heteronormative attitudes in the community. Biased heteronormative opinions are widespread throughout the community. The existence of these attitudes is nothing more than a continuation of the patriarchal ideologies inherent in cultural and political systems for centuries. This research uses qualitative analysis methods and contains a number of intrinsic elements in the form of characters and characterizations, settings, and plot as well as extrinsic elements, namely the perspective of cultural studies focused on patriarchal concepts and feminism. The results of the research prove that gender discrimination can be eradicate and women should fight to get their rights back.Keywords : discrimination; patriarchal concepts; feminism.